Mercury‐Free Synthesis of Pincer [C^N^C]AuIII Complexes by an Oxidative Addition/CH Activation Cascade. Issue 8 (24th March 2020) - Eppel, Daniel; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K.
Abstract: Starting from the commercially available dimethyl sulfide‐gold(I) chloride complex (DMSAuCl) and diazonium salts in the presence of 2, 6‐di‐ tert ‐butyl‐4‐methylpyridine as base, symmetric and unsymmetric [C^N^C]Au III Cl complexes were synthesized in a selective, photosensitizer‐free, photochemical reaction using blue LED light. This new protocol provides the first mercury‐free synthesis of these types of pincer‐complexes in moderate‐to‐excellent yields, starting from a readily available gold(I) precursor. Owing to the extraordinary properties of the target compounds, like excellent luminescence and high anticancer activities, the synthesis of such complexes is a highly active field of research, which might make its way to an industrial application. Owing to the disadvantages of the known protocols, especially the toxicity and the selectivity issues in the case of unsymmetric complexes, avoiding the use of mercury, should further accelerate this ongoing development. Abstract : Non‐toxic route : A flexible photochemical approach with high functional‐group tolerance avoids the use of toxic mercury in the preparation of organogold(III) C^N^C pincer complexes. The precursors are readily available starting materials.